Modeling Salinity Propagation in Cikarang Bekasi Laut Channel, Bekasi Regency, West Java Province, Indonesia - Harman Ajiwibowo; Munawir Bintang Pratama (Journal of Engineering and Technological Sciences, 2022)
An inland waterway will be constructed in an existing channel in West Java, Indonesia. The change of salinity in a river due to capital dredging is investigated using a finite element modeling system. The location of the research is the Cikarang Bekasi Laut (CBL) channel, Bekasi Regency, West Java, Indonesia. The aim of this study is to simulate salinity propagation in the CBL before and after capital dredging. Salinity modeling is carried out using the Surface-water Modeling System (SMS). Field surveys of the topography, bathymetry, currents and water level are conducted for the model. The model results are validated with the current and water level field measurements. The field and model results agree well. The current and salinity results show that the trends are correlated with river discharges. After the capital dredging, the salinity in the CBL increases. Mitigation is carried out by constructing a check dam, which can reduce the average salinity in the upstream region by up to 0.05 ppt during the wet season and up to 0.12 ppt during the dry season.